1998
DOI: 10.1097/00004872-199816060-00015
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and endothelin-1 receptor antagonists have cumulative hypotensive effects in canine Page hypertension

Abstract: The cumulative hypotensive effect of bosentan suggests that, besides angiotensin II, endothelin-1 is independently involved in the pathophysiology of hypertension, which presents new therapeutic perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…21 The lack of effect of ET-1 antagonism on BP and CVD is in accord with the observation that ET-1 mRNA was evidently increased in cardiovascular tissues only in the late phase of 2-kidney, 1-clip hypertension, indicating that ET-1 might attain increasing importance in the non-renin-dependent late phase of the initially renin-dependent forms of hypertension. 19 This contention is also in agreement with data involving a chronic canine Page model of hypertension, 43 which had high Ang II levels and in which bosentan lowered BP when it was administered after losartan. Thus, apart from the obvious differences between exogenously and endogenously borne Ang II, 1,4 it might be reasonable to assume that ET-1 becomes involved in the more advanced stages of hypertension, when endothelial dysfunction is a hallmark.…”
Section: Discussionsupporting
confidence: 84%
“…21 The lack of effect of ET-1 antagonism on BP and CVD is in accord with the observation that ET-1 mRNA was evidently increased in cardiovascular tissues only in the late phase of 2-kidney, 1-clip hypertension, indicating that ET-1 might attain increasing importance in the non-renin-dependent late phase of the initially renin-dependent forms of hypertension. 19 This contention is also in agreement with data involving a chronic canine Page model of hypertension, 43 which had high Ang II levels and in which bosentan lowered BP when it was administered after losartan. Thus, apart from the obvious differences between exogenously and endogenously borne Ang II, 1,4 it might be reasonable to assume that ET-1 becomes involved in the more advanced stages of hypertension, when endothelial dysfunction is a hallmark.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with previously reported findings on the effects of administration of losartan in rats and pigs (Pals & Couch, 1993;Molinari et al 2001). The dose of losartan used in the present study has been shown to block the pressor effect of renovascular hypertension in dogs (Massart et al 1998), and has been previously used in anaesthetized pigs to block angiotensin II receptors (Molinari et al 2000(Molinari et al , 2001. Moreover, the same dose has been shown in the same experimental model as the present study to reduce by about 50 % the pressor response to angiotensin II infusion without causing significant effects on baseline values of arterial blood pressure (Molinari et al 2001).…”
Section: Figuresupporting
confidence: 94%
“…AT 1 receptors alone, indicating that combined blockade could have added benefit in patients with hypertension (18).…”
Section: Integrated Regulation Of Resistance Vessel Tone By Et and Anmentioning
confidence: 99%